An investigation into the present condition and biomolecular activities of Bangladeshi seaweed with deadly diseases: a review - Mukta, Habiba Anjuman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirement for the degree of Master of Science in Biotechnology, 2024.